Application of quantitative microbial risk assessment to analyze the public health risk from poor drinking water quality in a low income area in Accra, Ghana - Machdar, E.; Steen, N.P. van der; Raschid-Sally, Liqa; Lens, P.N.L. (Elsevier, 2013)
In Accra, Ghana, a majority of inhabitants lives in over-crowded areas with limited access to piped water supply, which is often also intermittent. This study assessed in a densely populated area the risk from microbial contamination of various sources of drinking water, by conducting a Quantitative Microbiological Risk Assessment (QMRA) to estimate the risk to human health from microorganism exposure and dose-response relationships. Furthermore the cost-effectiveness in reducing the disease burden through targeted interventions was evaluated. Five risk pathways for drinking water were identified through a survey (110 families), namely household storage, private yard taps, communal taps, communal wells and water sachets. Samples from each source were analyzed for Escherichia coli and Ascaris contamination. Published ratios between E. coli and other pathogenswere used for theQMRA and disease burden calculations. The major part of the burden of disease originated from E. coli O157:H7 (78%) and the least important contributor was Cryptosporidium (0.01%). Other pathogens contributed 16% (Campylobacter), 5% (Rotavirus) and 0.3% (Ascaris). The sum of the disease burden of these pathogens was 0.5 DALYs per person per year, which is much higher than the WHO reference level. The major contamination pathway was found to be household storage. Disinfection of water at household level was the most cost-effective intervention (b5 USD/DALY-averted) togetherwith hygiene education.Water supply network improvements were significantly less cost-effective.